Quartz Crystal Microbalance a Powerful Technique for Nanogram Mass Sensing - Sivar Aziz Baiz; Payam Najmaddin; Azeez A. Barzinjy (Eurasian Journal of Science and Engineering, 2022)
A quartz crystal microbalance (QCM) is an acoustic transducer that sends an electronic signal when a mass change is detected on the sensor surface of an oscillating quartz-crystal resonator. QCM can detect a small amount of materials in the nanogram range quantitatively from the shift in resonance frequency under vacuum, gas phase, and a liquid environment. QCM is produced by oscillating a piezoelectric, single-crystal quartz plate to measure mass. Quartz’s inherent property of piezoelectricity is the basis of QCM operation. This paper aims to review the role of quartz crystal microbalance in nanotechnology as mass sensing. One of the fundamental driving forces in nanotechnology that positively impact related research areas is new measurement techniques.